The diffusion of ecstasy through urban youth networks. - Schensul, Jean J; Diamond, Sarah; Disch, William; Bermudez, Rey; Eiserman, Julie (Journal of ethnicity in substance abuse, 2005)
Ecstasy is a drug commonly associated with all-night, or all-weekend electronic dance events known as raves. Upper- and middle-class clubs, gay bars and clubs, and party venues are other common public settings where ecstasy use occurs. During the mid to late 1990s its use was reported in locations as distant as Australia and New Zealand, England and Scotland, and North America. In the United States, use increased dramatically at the end of the millennium, and drug monitoring systems began to report its presence among urban youth. Using social influence, social marketing and diffusion theory, this paper outlines the micro-level processes through which ecstasy traveled from downtown clubs catering to suburban young adults through urban youth networks through distributors and users. The paper is based on participant observation, and in-depth interviews with dealers and users collected during the period of peak diffusion 1999-2001, and survey data collected from 401 poly-drug users between the ages of 16 and 24 and collected at two time points from 1999-2002.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Amphetamine-Related Disorders; Connecticut; Cross-Cultural Comparison; Cross-Sectional Studies; Cultural Diversity; Drug Contamination; Drug Interactions; European Continental Ancestry Group; Female; Health Surveys; Hispanic Americans; Humans; Male; Motivation; N-Methyl-3,4-methylenedioxyamphetamine; Social Facilitation; Social Support; Socioeconomic Factors; Street Drugs; Urban Population